2019
DOI: 10.1007/s00259-019-04300-z
|View full text |Cite
|
Sign up to set email alerts
|

Digital PET/CT: a new intriguing chance for clinical nuclear medicine and personalized molecular imaging

Abstract: Clinical PET/CT is a well-known useful tool for the in vivo noninvasive quantitative imaging of physiologic and pathologic processes [1]. Actually, the key role of PET/CT in cancer staging and therapeutic responses to personalized treatments is well established; it is an essential imaging modality not only in oncology but also in neuroscience and in all the applications of molecular imaging. In recent years, there have been multiple advances in PET/CT scanners: new hardware, software, and acquisition methods t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…As described in the introduction, digital PET/CT represents a step forward in molecular imaging, with increasing numbers of publications confirming the favourable performance characteristics for such scans in comparison to previous-generation analogue systems [ 1 , 16 ], including increased lesion detection and sensitivity [ 1 , 3 , 4 , 13 , 17 ]. Previous authors have reported head-to-head studies comparing digital and analogue systems, showing both improved image quality and upstaging of individuals [ 10 ], as well as improved recovery (as shown by higher SUV values) and lesion sharpness [ 3 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…As described in the introduction, digital PET/CT represents a step forward in molecular imaging, with increasing numbers of publications confirming the favourable performance characteristics for such scans in comparison to previous-generation analogue systems [ 1 , 16 ], including increased lesion detection and sensitivity [ 1 , 3 , 4 , 13 , 17 ]. Previous authors have reported head-to-head studies comparing digital and analogue systems, showing both improved image quality and upstaging of individuals [ 10 ], as well as improved recovery (as shown by higher SUV values) and lesion sharpness [ 3 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The administered activity should be the lowest possible dose that will produce diagnostic image quality. This, in part, depends on the acquisition techniques and the sensitivity of the PET/CT scanner (76)(77)(78)(79). The administered activity should follow the 2016 Update of the North American Consensus Guidelines for Pediatric Administered Radiopharmaceutical Activities and the 2016 EANM pediatric Dosage Card (80)(81)(82).…”
Section: Radiopharmaceuticalsmentioning
confidence: 99%
“…To reduce the radiation dose, a groundbreaking improvement in PET technology is necessary. Digital PET is a good example of successful dose reduction due to the enhanced sensitivity from using a PET equipped with digital silicon photomultipliers [ 121 ]. The high sensitivity of digital PET makes it possible to acquire images either with a shorter scan time or with a lower radiopharmaceutical dose.…”
Section: Discussion and Summarymentioning
confidence: 99%